Plant diversity enhances moth diversity in an intensive forest management experiment. Issue 1 (4th January 2017) - Root, Heather T.; Verschuyl, Jake; Stokely, Thomas; Hammond, Paul; Scherr, Melissa A.; Betts, Matthew G.
Abstract: Intensive forest management (IFM) promises to help satisfy increasing global demand for wood but may come at the cost of local reductions to forest biodiversity. IFM often reduces early seral plant diversity as a result of efforts to eliminate plant competition with crop trees. If diversity is a function of bottom‐up drivers, theory predicts that specialists at lower trophic levels (e.g., insect herbivores) should be particularly sensitive to reductions in plant diversity. We conducted a stand‐level experiment to test bottom‐up controls on moth community structure, as mediated by degrees of forest management intensity. Using a dataset of 12, 003 moths representing 316 moth species, moth richness decreased only slightly, if at all, as herbicide intensity increased ( P = 0.062); the moderate treatment, which is most commonly applied in the northwestern USA, was estimated to have 4.72 (±2.14 SE, P = 0.039) fewer species than the control. Structural equation modeling revealed strong support for an effect of herbicide on plant abundance, which influenced plant species richness and subsequently moth species richness. Moth species richness was associated with plant species richness and followed a power law function ( z = 0.42, P = 0.006), which is surprisingly consistent with a recent large‐scale experiment in agricultural systems, and provides support for bottom‐up drivers of moth community structure. Moth abundance was not influenced by the direct effects of silvicultural herbicide treatments. Site‐level effects and variation in pre‐harvest vegetation communities resulted in residual broadleaf and herbaceous vegetation in even the most intensive treatment. Even at low densities, these residual deciduous and herbaceous plants supported higher than expected moth abundance and richness. We conclude that forest management practices that retain early seral vegetation diversity are the most likely to conserve moth communities.